(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Examining the impact of marketing strategies on the growth and sustainability of food enterprises owned by women in the Ernakulam District. Marketing strategy helps the firm by coming up with plans to choose the proper customers, establish trustworthy connections with them, and generate growth.